2010
DOI: 10.1038/nature08695
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous non-retroviral RNA virus elements in mammalian genomes

Abstract: Retroviruses are the only group of viruses known to have left a fossil record, in the form of endogenous proviruses, and some of 8% of the human genome is made up of these elements 1,2 . Although many other viruses, including non-retroviral RNA viruses, are known to generate DNA forms of their own genomes during replication3 , 4, none has been found as DNA in the germline of animals. Bornaviruses, a nonsegmented, negative-sense RNA virus, are unique among RNA viruses in that they establish persistent infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
480
4
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 413 publications
(508 citation statements)
references
References 27 publications
14
480
4
10
Order By: Relevance
“…Furthermore, although it has been shown that endogenization could be catalysed by host retrotransposons [44], we did not detect any molecular signature (such as target-site duplications) indicating involvement of such mobile elements in snake EVEs endogenization.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Furthermore, although it has been shown that endogenization could be catalysed by host retrotransposons [44], we did not detect any molecular signature (such as target-site duplications) indicating involvement of such mobile elements in snake EVEs endogenization.…”
Section: Resultsmentioning
confidence: 48%
“…In addition to a nucleoprotein, the genome of bornaviruses encodes five other proteins (a phosphoprotein, a matrix protein, a glycoprotein, an RNA-dependent RNA polymerase and an accessory protein). Several endogenous fragments of the matrix, RNApolymerase and glycoprotein genes have been discovered in the genomes of a number of other vertebrate species [1,12,28,44]. Most endogenous bornaviruses reported to date correspond to the nucleoprotein, which may be owing to the existence of a 3 0 -5 0 transcription gradient of bornavirus genomes, resulting in a higher abundance of nucleoprotein mRNA [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the underlying mechanisms are unknown, it was discovered that the human genome contains bits and pieces of non-retrovirus RNA viruses [55,56]. A clue to the mechanism might be found in Drosophila, where in cells such integration was shown to be achieved by the reverse transcriptase activity of transposons, resulting in establishment of an anti-viral RNAi response [57].…”
Section: Manipulation Of Transgenerational Immunitymentioning
confidence: 99%